TEACHING READING NARRATIVE TEXTS THROUGH UNCOVER CONCENTRATE MONITOR EVALUATE (U-C-ME) STRATEGY - Yuspar Uzer; Yusver Nandes Uzer (HOLISTICS, 2020)
Abstract: The objective of the study was to find out whether or not it is effective to teach readingnarrative texts through Uncover Concentrate Monitor Evaluate (U-C-Me) strategy to the tenthgrade students of State Senior High School 8Palembang. In data analysis, it found that the result ofpaired sample, the result of t-obtained was 26.64, where the value of t-table was 1.671 atsignificance level of 0.05 and with one tailed testing. Since the value of t-table obtained was lowerthan the value of t-table (26.64 < 1.671) consequently the null hypothesis (Ho) was rejected andalternative hypothesis was accepted and the result of t-obtained was 5.09 at significance level of0.05 and with one tailed testing. Since the value of t-obtained was higher than the value of t-table(5.09 > 1.671) consequently the null hypothesis (Ho) was rejected and the alternatif hypothesis(Ha) was accepted. It means that it was effective to teach reading narrative texts through UncoverMonitor Evaluate (U-C-ME) strategy to the tenth grade students of state Senior High School 8Palembang.